Superficial Bladder Cancer Therapy - Emmanuel Schenkman; Donald L. Lamm (The Scientific World Journal)
Bladder cancer treatment remains a challenge despite significant improvements in preventing disease progression and improving survival. Intravesical therapy has been used in the management of superficial transitional cell carcinoma (TCC) of the urinary bladder (i.e. Ta, T1, and carcinoma in situ) with specific objectives which include treating existing or residual tumor, preventing recurrence of tumor, preventing disease progression, and prolonging survival. The initial clinical stage and grade remain the main determinant factors in survival regardless of the treatment. Prostatic urethral mucosal involvement with bladder cancer can be effectively treated with Bacillus Calmette-Guerin (BCG) intravesical immunotherapy. Intravesical chemotherapy reduces short-term tumor recurrence by about 20%, and long-term recurrence by about 7%, but has not reduced progression or mortality. Presently, BCG immunotherapy remains the most effective treatment and prophylaxis for TCC (Ta, T1, CIS) and reduces tumor recurrence, disease progression, and mortality. Interferons, Keyhole-limpet hemocyanin (KLH), bropirimine and Photofrin-Photodynamic Therapy (PDT) are under investigation in the management of TCC and early results are encouraging. This review highlights and summarizes the recent advances in therapy for superficial TCC.